Calculation of temperature fields and thermal stresses in the growing skin in steel casting at the section continuous casting machines - V. M. Olshanski; V. I. Timoshpolski; N. P. Koval; I. A. Trusova; V. V. Filippov (Литьë и металлургия)
The article describes а new approach to determination of the boundary conditions in solution of the problem of solidification and cooling of billets in casting at the section continuous casting machine. Quantitative evaluation of thermal stresses in the solidified billet skin in given.